Cross-ministry data on service use and limitations faced by children in special education. Issue 4 (October 2021) - Russell, Matthew Joseph; Michael Scott, Craig William; Murias, Kara; Ben Gibbard, W.; Cui, Xinjie; Tough, Suzanne; Zwicker, Jennifer D.
Abstract: Background: Children with disabilities often face limitations that cross support sectors. Objective : Our aim was to measure cross-ministry service use, outcomes, and functional limitations faced by children who qualified for special education. Methods: We used longitudinal British Columbia ministry data linked to children (0-18y) registered in K-12 education. Children were grouped by special education funding (most to least; Level 1, Level 2, Level 3, Unfunded, and no special education), and related to 1) service use patterns, 2) the age they first used disability services, and 3) functional limitations reported in health visits. We also reported how length of special education use related to disability service use. Results: Of 111, 274 children, 154(0.1%) were Level 1, 4427(4.0%) Level 2, 2897(2.6%) Level 3, 13472(12.1%) Unfunded, and 90324(81.2%) not in special education. Children with higher funding levels, compared to lower levels of funding, generally were more likely to experience poorer outcomes, have functional limitations, have service needs, and receive early support. One exception was children with serious behavioral/mental health special education coding, which had poorer outcomes for their level of funding. Children received child disability supports early (about half of users started by 4y), but use was mostly limited to those with many years (9+years) of funded special education (70.7% of the all users) and biased to certain special education codes (i.e., Level 1, severe intellectual disability, and autism). Conclusions: This study provides evidence of the long-term, diverse needs of children in special education and may be used to inform decisions surrounding their support.